Information Warfare in International Relations: The Information War in the Digital Age - Fitri Arianti (Pt. Anagata Sembagi Education, 2026)
This article examines the phenomenon of information warfare in contemporary international relations, focusing on how state and non-state actors exploit digital technologies to influence public perceptions, destabilize democratic institutions, and achieve geopolitical objectives. Through a systematic literature review of leading publications from 2021 to 2024, the study identifies three principal dimensions of modern information warfare: disinformation and social media manipulation, cyber operations against critical infrastructure, and the use of artificial intelligence in cognitive and military decision-making domains. Findings indicate that technological advances, particularly deepfakes, OODA loop automation, and quantum computing, significantly expand the scope and effectiveness of information operations, while defensive mechanisms such as digital literacy and cyber diplomacy continue to face substantial implementation gaps.